THE JOURNEY OF TEACHING NON-ENGLISH SPEAKING LEARNERS FROM A FOREIGN COUNTRY - Linnette A Ejem; Iris April L. Ramirez; Cesar B Ortiz (State Islamic University of North Sumatra Indonesia, 2017)
The study explored the experiences of the Trainers during their conduct of Summer Training with Thai Elementary teachers on May 2016 and April 2017 at Bukidnon State University (BukSU), Malaybalay City, Philippines. The Summer Training was conducted to teach the Thai teachers English Communication Arts; Mathematics and Science using English language. The challenges, difficulties and problems encountered by the BukSU Trainers in training Thai Teacher-Trainees as English second language (ESL) learners, were determined as well as the interventions utilized by the Trainers to address their encountered challenges/difficulties/problems. Narrative qualitative analysis was employed to gather data. From the narratives of the Trainers, trends and patterns were established to analyze and interpret the results. Data revealed that the encountered challenges by BukSU Trainers in training the Thai Trainees include language barrier, the Trainees’ difficulty in understanding English language and how to effectively teach content in math and science using English language. The difficulties/problems encountered by the Trainers were addressed through teaching strategies and approaches that promoted active participation; involved minds-on, hands-on, and experiential learning activities; and exposed the Thai Teacher-Trainees to real-life situations.